Resin composition, and molded article

By adding a phosphate with a pH of less than 7 to a resin composition of polycarbonate resin and titanium oxide, the issues of reduced impact strength and yellowing in molded products are addressed, resulting in improved performance and stability.

JP2025040777APending Publication Date: 2025-03-25MITSUBISHI ENG PLASTICS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023147792
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The blending of titanium oxide with polycarbonate resin results in molded products with inferior impact strength and a tendency to yellow when the residence time is long during molding.

Method used

Incorporating a predetermined amount of phosphate with a pH of less than 7 into the resin composition containing polycarbonate resin and titanium oxide, which helps to enhance impact resistance and prevent yellowing of the molded product.

Benefits of technology

The resin composition achieves excellent impact resistance and effectively suppresses the yellowing of molded products, even under prolonged residence times during molding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040777000001
    Figure 2025040777000001
  • Figure 2025040777000002
    Figure 2025040777000002
Patent Text Reader

Abstract

To provide a resin composition containing a polycarbonate resin and titanium oxide which can provide a molded article that is excellent in impact resistance and effectively suppresses yellow discoloration of the obtained molded article, and a molded article.SOLUTION: A resin composition contains, with respect to 100 pts.mass of a polycarbonate resin (A), 5.0 pts.mass or more and 20.0 pts.mass or less of titanium oxide particles (B), and 0.3 pts.mass or more and 3.0 pts.mass or less of phosphate (C) having a pH of less than 7.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article, and in particular to a resin composition containing a polycarbonate resin as a main component. [Background technology]

[0002] 2. Description of the Related Art Titanium oxide has conventionally been blended into polycarbonate resin for the purpose of improving the shielding properties and coloring of resin molded products (Patent Document 1, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 172243 [Patent Document 2] JP 2019-123809 A Summary of the Invention [Problem to be solved by the invention]

[0004] As mentioned above, titanium oxide particles may be blended into a resin composition containing a polycarbonate resin. However, when titanium oxide is blended into a polycarbonate resin, the impact strength of a molded article obtained from the resin composition tends to be poor. In addition, when the residence time during molding is long, the molded article obtained may turn yellow. The present invention aims to solve the above problems, and to provide a resin composition containing a polycarbonate resin and titanium oxide, which is excellent in impact resistance and can provide a molded article in which yellowing of the obtained molded article is effectively suppressed, and a molded article. [Means for solving the problem]

[0005] In light of the above-mentioned problems, the present inventors have conducted research and found that the above-mentioned problems can be solved by further blending a predetermined amount of a phosphate having a pH of less than 7 into a resin composition containing a polycarbonate resin and titanium oxide. Specifically, the above problems were solved by the following means. <1> For 100 parts by mass of polycarbonate resin (A), Titanium oxide particles (B) of 5.0 parts by mass or more and 20.0 parts by mass or less; Contains 0.3 parts by mass or more and 3.0 parts by mass or less of a phosphate (C) having a pH of less than 7, Resin composition. <2> The phosphate (C) comprises an inorganic phosphate; <1> The resin composition according to claim 1. <3> A light guide base for an automobile light or a light guide base for lighting. <1> or <2> The resin composition according to claim 1. <4> The phosphate (C) contains an inorganic phosphate, and is used for a light guide base for an automobile lamp or a light guide base for lighting. <1> ~ <3> 10. The resin composition according to claim 9 . <5> <1> ~ <4> 2. A pellet of the resin composition according to claim 1. <6> <1> ~ <4> 2. A molded article formed from the resin composition according to claim 1. <7> <5> A molded article formed from the pellets according to claim 1. Effect of the Invention

[0006] The present invention makes it possible to provide a resin composition containing a polycarbonate resin and titanium oxide, which is capable of providing a molded article that has excellent impact resistance and in which yellowing of the resulting molded article is effectively inhibited, and a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.

[0008] The resin composition of this embodiment is characterized in that it contains 5.0 parts by mass or more and 20.0 parts by mass or less of titanium oxide particles (B) and 0.3 parts by mass or more and 3.0 parts by mass or less of a phosphate salt (C) having a pH of less than 7, relative to 100 parts by mass of a polycarbonate resin (A). By using such a constitution, a resin composition capable of providing a molded product having excellent impact resistance can be obtained, and a resin composition capable of effectively suppressing a decrease in the YI value during retention molding can be obtained. In this embodiment, reactive hydroxyl groups may be exposed on the surface of the titanium oxide particles (B). Such hydroxyl groups damage the polycarbonate resin (A). In addition, the titanium oxide particles (B) may be surface-treated, but some of them are surface-treated in the state of secondary particles. Therefore, when a shear force is applied, the titanium oxide particles (B) become primary particles, and some of the hydroxyl groups of the titanium oxide particles (B) are exposed on the surface. In this embodiment, it is presumed that the phosphate ions in the phosphate salt (C) having a pH of less than 7 act on the hydroxyl groups exposed on the surface of the titanium oxide particles (B), thereby minimizing damage to the polycarbonate resin (A). Furthermore, by using a specific amount of phosphate (C) with a pH of less than 7, the increase in the YI value during retention could be suppressed. The present invention will be described in detail below.

[0009] <Polycarbonate resin (A)> The resin composition of the present embodiment contains a polycarbonate resin (A). Specifically, the polycarbonate resin (A) is not particularly limited as long as it contains a -[OR-OC(=O)]- unit (wherein R is an organic group, preferably a hydrocarbon group, more preferably an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure) containing a carbonate bond in the molecular main chain. In this embodiment, the polycarbonate resin (A) is preferably an aromatic polycarbonate resin, more preferably a polycarbonate resin having a bisphenol skeleton, and more preferably at least one of bisphenol A type polycarbonate resin, bisphenol C type polycarbonate resin, and bisphenol AP type polycarbonate resin, and more preferably a bisphenol A type polycarbonate resin. By using such a polycarbonate resin, better heat resistance and toughness can be achieved. In the present embodiment, the polycarbonate resin having a bisphenol skeleton preferably contains, of all structural units, 90 mol % or more of structural units having a bisphenol skeleton (preferably structural units having a bisphenol A type skeleton), and more preferably contains, of all structural units, 95 mol % or more of structural units having a bisphenol skeleton.

[0010] The viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 10,000 or more, more preferably 12,000 or more, and even more preferably 15,000 or more. By making it equal to or more than the lower limit, the durability of the molded article obtained tends to be further improved. The upper limit of the viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 35,000 or less, more preferably 32,000 or less, and even more preferably 30,000 or less. By making it equal to or less than the upper limit, the molding processability of the molded article tends to be further improved. The viscosity average molecular weight (Mv) was calculated by using methylene chloride as a solvent and an Ubbelohde viscometer to determine the intrinsic viscosity [η] (unit: dL / g) at 25°C, and then using the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 ×Mv 0.83 , means a value calculated from When two or more types of polycarbonate resins are used, the viscosity average molecular weight is the mixture.

[0011] The method for producing the polycarbonate resin (A) is not particularly limited, and polycarbonate resins produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) can be used. When the melting method is used, a polycarbonate resin having an adjusted amount of OH groups at the terminal groups can be used.

[0012] The polycarbonate resin (A) used in this embodiment may be a recycled polycarbonate resin product (including recovered products, material recycled products, chemical recycled products, etc.), a rejected product, or a scrap from thermoplastic resin molding.

[0013] In addition to the above, details of the polycarbonate resin (A) can be referred to in paragraphs 0013 to 0041 of JP 2021-084942 A and in paragraphs 0030 to 0035 of JP 2021-119211 A, the contents of which are incorporated herein by reference.

[0014] The proportion of the polycarbonate resin (A) in the resin composition of this embodiment is preferably 83% by mass or more, more preferably 85% by mass or more, and even more preferably 87% by mass or more. By making it equal to or more than the lower limit, the impact resistance of the obtained molded article tends to be improved. In addition, the proportion of the polycarbonate resin (A) in the resin composition of this embodiment is preferably 95% by mass or less, more preferably 93% by mass or less. By making it equal to or less than the upper limit, the light blocking property of the obtained molded article tends to be improved. The resin composition of the present embodiment may contain only one type of polycarbonate resin (A), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0015] <Titanium oxide particles (B)> The resin composition of the present embodiment contains titanium oxide particles (B). By containing titanium oxide particles (B), it is possible to impart color to the obtained molded article and achieve light-shielding properties. The titanium oxide particles (B) are usually particles having the highest titanium oxide content, and the proportion of titanium oxide in the titanium oxide particles (B) is 85.0% by mass or more, and preferably 90.0% by mass or more. An example of the titanium oxide particles (B) is one that contains 90.0 to 98.0 mass% TiO2 and Al2O3, preferably 90.0 to 98.0 mass% TiO2, Al2O3, and SiO2, and more preferably 90.0 to 98.0 mass% TiO2, 0.5 to 3.5 mass% Al2O3, and 0 to 6.0 mass% SiO2. Furthermore, the titanium oxide particles (B) may contain 0 to 0.1 mass% SO3, 0 to 0.15 mass% Na2O, and 0 to 0.01 mass% Cl in addition to the above components. Furthermore, the titanium oxide particles (B) may contain other components, the total of which is 100 mass%. Each component in the titanium particles (B) is measured by fluorescent X-rays and calculated in terms of oxide. Specifically, it is evaluated by semi-quantitative measurement. The total of the oxides is taken as 100% by mass, and the percentage of each oxide is expressed as a mass% value. For the measurement, a ZSX Primus manufactured by Rigaku Corporation can be used.

[0016] In this embodiment, the titanium oxide particles (B) may be either rutile type titanium oxide particles or anatase type titanium oxide particles. In addition, the titanium oxide particles (B) are preferably surface-treated with a surface treatment agent. By adopting such a constitution, the titanium oxide is more easily dispersed in the polycarbonate resin (A), and a molded article with a better appearance can be obtained. The surface treatment agent preferably contains the above-mentioned Al2O3 and / or SiO2. The surface treatment agent may be physically adsorbed or chemically bonded to the titanium oxide surface. The titanium oxide is usually titanium dioxide.

[0017] In this embodiment, the resin composition contains 5.0 to 20.0 parts by mass of titanium oxide particles (B) with respect to 100 parts by mass of the polycarbonate resin (A). By setting it to be below the upper limit value, the effect of suppressing the deterioration of physical properties during residence tends to be further improved. Also, by setting it to be above the lower limit value, the effect of improving light shielding property tends to be further improved. In this embodiment, the content of the titanium oxide particles (B) is preferably 6.0 parts by mass or more, more preferably 7.0 parts by mass or more, and even more preferably 9.0 parts by mass or more with respect to 100 parts by mass of the polycarbonate resin (A). In this embodiment, the content of the titanium oxide particles (B) is preferably 19.0 parts by mass or less, more preferably 18.0 parts by mass or less, further preferably 15.0 parts by mass or less, and even more preferably 12.0 parts by mass or less with respect to 100 parts by mass of the polycarbonate resin (A). The resin composition of this embodiment may contain only one kind of titanium oxide particles (B), or may contain two or more kinds. When containing two or more kinds, it is preferable that the total amount is within the above range.

[0018] <Phosphate (C) with pH less than 7> The resin composition of this embodiment contains a phosphate (C) with a pH less than 7. The pH of the phosphate (C) is less than 7, preferably 6 or less, more preferably 5 or less, further preferably 4.7 or less. Also, it is preferably 1 or more, more preferably 2 or more, further preferably 3 or more, even more preferably 3.5 or more, and even more preferably 4 or more. By setting it to be above the lower limit value, the decomposition of the polycarbonate resin can be effectively suppressed. Also, by setting it to be below the upper limit value, the effect of protecting the active surface of titanium oxide tends to be further improved. The pH value is measured at 25°C after adding 50 g of phosphate (C) with a pH of less than 7 to 1 L of water. If phosphate (C) does not dissolve in water, dissolve it in a water-miscible or water-immiscible solvent and measure the pH. When using a water-miscible solvent, immerse the electrode in the mixed solution to measure the pH. When using a water-immiscible solvent, use deionized water to perform a solvent extraction of the sample in the aqueous phase before measuring the pH.

[0019] The phosphate (C) having a pH of less than 7 may be an organic phosphate or an inorganic phosphate, but is preferably an inorganic phosphate. The metal constituting the phosphate is preferably an alkali metal salt and / or an alkaline earth metal salt, more preferably an alkali metal salt, further preferably sodium and / or potassium, and even more preferably sodium. Specifically, sodium dihydrogen phosphate and ammonium dihydrogen phosphate are exemplified, and sodium dihydrogen phosphate is preferred. The phosphate (C) having a pH of less than 7 may be a hydrate.

[0020] The content of the phosphate (C) having a pH of less than 7 in the resin composition of this embodiment is 0.3 parts by mass or more, preferably 0.4 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 0.8 parts by mass or more, and even more preferably 1.0 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). The content of the phosphate (C) having a pH of less than 7 is 3.0 parts by mass or less, preferably 2.8 parts by mass or less, more preferably 2.5 parts by mass or less, even more preferably 2.0 parts by mass or less, even more preferably 1.5 parts by mass or less, and even more preferably 1.2 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or more than the lower limit, the effect of protecting the active surface of titanium oxide tends to be further improved. Also, by making it equal to or less than the upper limit, the decomposition of the polycarbonate resin can be effectively suppressed.

[0021] In addition, the content of the phosphate (C) having a pH of less than 7 in the resin composition of this embodiment is preferably 0.1 mass% or more in the resin composition, more preferably 0.3 mass% or more, and even more preferably 0.8 mass% or more, and is preferably 3.0 mass% or less, and more preferably 1.5 mass% or less. The resin composition of the present embodiment may contain only one type of phosphate (C) having a pH of less than 7, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range. In addition, when the phosphate (C) having a pH of less than 7 is a hydrate, the amount of the phosphate (C) having a pH of less than 7 is the amount of the phosphate including the hydrate.

[0022] <Other ingredients> The resin composition of the present embodiment may contain other components as necessary, as long as the desired physical properties are not significantly impaired. Examples of the other components include various resin additives. Examples of resin additives include reactive compounds (e.g., epoxy compounds and / or oxetane compounds), stabilizers, release agents, ultraviolet absorbers, colorants (dyes, pigments), antistatic agents, flame retardants, flame retardant assistants, anti-dripping agents, anti-fogging agents, anti-blocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, etc. The resin additives may be contained alone or in any combination and ratio of two or more.

[0023] <<Stabilizer>> The resin composition of the present embodiment may contain a stabilizer. The stabilizers include heat stabilizers and antioxidants. Examples of the stabilizer include phenol-based, amine-based, phosphorus-based, and thioether-based stabilizers. Among these, in the present embodiment, it is preferable to include a phosphorus-based heat stabilizer.

[0024] Any known phosphorus-based heat stabilizer can be used. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.

[0025] Examples of the organic phosphite compound include distearyl pentaerythritol diphosphite, bis(decyl)pentaerythritol diphosphite, bis(tridecyl)pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB (registered trademark; the same applies below) 1178," "ADK STAB 2112," and "ADK STAB HP-10" manufactured by ADEKA Corporation, "JP-351," "JP-360," and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS (registered trademark; the same applies below) 168" manufactured by BASF.

[0026] As for the phosphorus-based heat stabilizer used in this embodiment, in addition to the above, the description in paragraphs 0127 to 0133 of JP 2022-067329 A can be referred to, the contents of which are incorporated herein by reference.

[0027] As the phenol-based antioxidant, a hindered phenol-based antioxidant is preferably used. Specific examples of hindered phenol-based antioxidants include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 4,6-bis(octyl butylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0028] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred. Specific examples of such hindered phenol-based antioxidants include "Irganox (registered trademark, the same applies below) 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA.

[0029] The content of the stabilizer in the resin composition of the present embodiment is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin. By setting the content of the stabilizer within the above range, the effect of adding the stabilizer is more effectively exhibited. The resin composition of the present embodiment may contain only one type of stabilizer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0030] <<Release agent>> The resin composition of the present embodiment may contain a mold release agent. By blending the mold release agent, the mold releasability can be further improved. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, ketone waxes, and light amides. Of these, aliphatic carboxylic acids, salts of aliphatic carboxylic acids, and esters of aliphatic carboxylic acids and alcohols are preferred. For details about the release agent, please refer to paragraphs 0055 to 0061 of JP2018-095706A, the contents of which are incorporated herein by reference. When the resin composition of the present embodiment contains a release agent, the content thereof in the resin composition is preferably 0.01 to 3 mass %. The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0031] <Method of producing resin composition> The method for producing the resin composition of the present embodiment is not limited, and a wide variety of known methods for producing resin compositions can be used. For example, the polycarbonate resin (A), titanium oxide particles (B), phosphate (C) having a pH of less than 7, and other components to be mixed as necessary are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The temperature for melt-kneading is not particularly limited, but is usually in the range of 240 to 320°C.

[0032] <Molded products> The molded article of this embodiment is formed from the resin composition or pellets of this embodiment. The above-mentioned resin composition (for example, pellets) is molded into a molded article by various molding methods. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article, and examples thereof include film-like, rod-like, cylindrical, ring-like, circular, elliptical, polygonal, irregular, hollow, frame-like, box-like, panel-like, and button-like shapes.

[0033] The method for forming the molded article is not particularly limited, and a conventionally known molding method can be adopted, for example, injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding) molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, pressure molding, etc. In particular, the resin composition of this embodiment is suitable for molded articles obtained by injection molding, injection compression molding, and extrusion molding. However, it goes without saying that the resin composition of this embodiment is not limited to molded articles obtained by these methods.

[0034] The molded article of this embodiment can be widely used for molded articles containing polycarbonate resin, particularly optical parts. Specifically, it is preferably used in electrical / electronic equipment / parts, OA equipment / parts, information terminal equipment / parts, machine parts, home appliances, vehicle parts, building materials, various containers, leisure goods / miscellaneous goods, lighting equipment, etc., and more specifically, it is preferably used for power covers, lighting lenses, lighting covers, light guiding members, etc. More specifically, it can be used for light guides and lenses that guide light from light sources such as LEDs in headlamps, rear lamps, fog lamps, etc. for vehicles such as automobiles and motorcycles. In particular, it can be preferably used for light guide bases for automobile lighting or light guide bases for lighting. For the use of the resin composition of this embodiment, in addition to the above, the descriptions in paragraphs 0098 to 0105 of JP 2020-189992 A can be referred to, the contents of which are incorporated herein by reference. EXAMPLES

[0035] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.

[0036] 1.Raw materials The raw materials shown in Table 1 below were used. [Table 1]

[0037] 2. Examples 1 to 6 and Comparative Examples 1 to 4 <Compound> Each component described in Table 1 (polycarbonate resin (A), titanium oxide particles (B), and phosphate (C)) was blended so as to have the ratios (unit: parts by mass) described in Table 3, and uniformly mixed using a tumbler mixer to obtain a mixture. The polycarbonate was adjusted so that the melt volume rate (MVR, 300 °C, 1.2 kgf) was 17.5 cm 3 / 10 min using (A1) and (A2). The mass ratio of polycarbonate resin (A1) to polycarbonate resin (A2) was about 77:13. This mixture was supplied to a single-screw extruder "VS40-32V" manufactured by Tanabe Plastics Machinery Co., Ltd., kneaded under the conditions of a screw rotation speed of 80 rpm, a discharge rate of 20 kg / hr, and a barrel temperature of 250 °C, and extruded in a strand shape from the tip of the extrusion nozzle. The extrudate was rapidly cooled in a water tank and cut using a pelletizer to obtain pellets of the resin composition.

[0038] <Charpy impact strength (molding temperature 310 °C, residence time 7 min)> After drying the pellets obtained above at 120 °C for 5 hours, they were weighed using an injection molding machine ("EC75" manufactured by Shibaura Machine Co., Ltd.) at a cylinder temperature of 310 °C, a mold temperature of 80 °C, and a screw rotation speed of 80 rpm, retained in the cylinder for 7 minutes, and then injection molded under the condition of an injection speed of 30 mm / s to produce ISO multipurpose test pieces (3.0 mmt). The ISO standard multipurpose test pieces (ISO 3167 type A) obtained by the above method were notched using a notching machine ("Notching Tool A-4 type" manufactured by Toyo Seiki), with a single-tooth V cutter (45°, R = 0.25 mm), a notch rotation speed of 300 rpm, and the number of notch cutting times being 3 times, and at the same time, the center part was cut out by 80 mm using a slicer. The Charpy impact strength of the obtained notched Charpy test pieces was measured in accordance with ISO 179 (unit: kJ / m 2 ). The measurement was carried out using a Charpy impact tester DG-CB manufactured by Toyo Seiki at a measurement temperature of 23 °C.

[0039] <YI increase suppression rate (YI improvement rate)> The pellets obtained above were weighed out in an injection molding machine (Shibaura Machine Co., Ltd., "EC75") at a cylinder temperature of 310°C, a mold temperature of 80°C, and a screw rotation speed of 80 rpm. The pellets were allowed to remain in the cylinder for 30 seconds, 8 minutes, 16 minutes, 24 minutes, and 32 minutes, and then injection molded at an injection speed of 30 mm / s to produce 3.0 mmt plates. The color difference of each plate obtained above was measured using a color difference meter (Nippon Denshoku "SE6000") with a C light source and a viewing angle of 2 degrees, and the YI was calculated in accordance with ASTM D1925. YI improvement effect = [(YI of phosphate-added system - YI of phosphate-free system) / YI of phosphate-free system] x 100 (unit: %) The YI of the phosphate-added system is the YI value of the plate obtained using the pellets of the Example, and the YI of the phosphate-free system is the YI value of the plate obtained using the pellets of the Comparative Example in which the phosphate is removed from the corresponding Example. That is, in the case of Example 1, the YI improvement effect is calculated based on each YI value of Example 1 and the YI value of Comparative Example 1.

[0040] [Table 2]

[0041] As is clear from the above results, the molded article formed from the resin composition of the present invention has excellent impact resistance and can effectively suppress an increase in YI, particularly when the residence time is long.

Claims

1. For 100 parts by mass of polycarbonate resin (A), Titanium oxide particles (B) of 5.0 parts by mass or more and 20.0 parts by mass or less; Contains 0.3 parts by mass or more and 3.0 parts by mass or less of a phosphate (C) having a pH of less than 7; Resin composition.

2. The resin composition according to claim 1 , wherein the phosphate (C) comprises an inorganic phosphate.

3. The resin composition according to claim 1, which is used for a light guide base for an automobile lamp or a light guide base for lighting.

4. The resin composition according to claim 1, wherein the phosphate (C) contains an inorganic phosphate and is for a light guide base for an automobile lamp or a light guide base for lighting.

5. A molded article formed from the resin composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Polycarbonate resin composition and molded article

    JP2019123809A

  • Transparent resin composition, resin molded body, lamp cover, lamp cover for vehicles, combination lamp cover, and vehicle

    WO2019172243A1